TRANSPORTASI SEDIMEN PANTAI PADANG SUMATERA BARAT - Triyatno Triyatno (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
Abstract This research was conducted in the Padang beach with of aims are to determine wave characteristic and transportation sediment in the research area. The method in the research is area sampling, with point samples based different shore line. The research showed are different wave characteristics abaout long wave is 505,44 m – 898,56 m, wave higth 0,95 m – 1,60 m, wave period 17 second – 24 second, and wave energy 1,808 - 2,460 kg/s2 . Sediment transport in the research area can show for total sediment that carring of wave in the beach as 1437,14 m3/days in the Pasir Jambak, and 614,70 m3/days in the Pantai Beremas. Different transportation sediment in the research area for depended sediment matter that bring of rivers